2015
DOI: 10.1021/acs.est.5b00234
|View full text |Cite
|
Sign up to set email alerts
|

Higher PBDE Serum Concentrations May Be Associated with Feline Hyperthyroidism in Swedish Cats

Abstract: Serum from 82 individual cats was analyzed for decabromobiphenyl (BB-209), polybrominated diphenyl ethers (PBDEs), hydroxylated PBDEs (OH-PBDEs), and 2,4,6-TBP in order to study differences in body burden between healthy and sick cats diagnosed with Feline Hyperthyroidism (FH). Within the study group, 60 of these cats had a euthyroid (n = 23) or hyperthyroid (n = 37) status, all of which were used in the comparison. This study shows that hyperthyroid compared to euthyroid cats have higher serum concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 48 publications
(91 reference statements)
6
46
1
Order By: Relevance
“…In cats there were indications of an association between elevated BDE concentrations and hyperthyroidism (NORRGRAN et al, 2015), which we did not find in our study. We did not measure metabolites of BDE-s, but hydroxylated BDEs would probably correlate better than the parent compounds as they are more potent TH disruptors than the parent compounds (CHEVRIER, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…In cats there were indications of an association between elevated BDE concentrations and hyperthyroidism (NORRGRAN et al, 2015), which we did not find in our study. We did not measure metabolites of BDE-s, but hydroxylated BDEs would probably correlate better than the parent compounds as they are more potent TH disruptors than the parent compounds (CHEVRIER, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…These include elevated PBDEs in dust from houses containing hyperthyroid cats [35] and altered ratios of BDE100/BDE99 in hyperthyroid cats [26]. Recently, Norrgran et al [39] identified three BDE congeners (BDE99, BDE153, and BDE183) and one PCB congener (PCB153) that were significantly higher in hyperthyroid cats than control cats in Sweden. There are a number of factors that may account for the variability in previously reported results and may confound future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Among the remaining fourteen congeners that were not significantly elevated in the hyperthyroid group, six had the same pattern of halogenation. However, two of these congeners (PCB175 and PCB176) had p -values that were near significant (0.055 and 0.071, respectively) and another three (BDE99, BDE153, and BDE183) were previously identified as being elevated in a group of hyperthyroid cats [39]. It is possible that a study with a larger sample size may show an association between these congeners and feline hyperthyroidism; however, a more robust structure-activity relationship analysis would be necessary to determine whether this halogenation pattern contributes to the ability of specific PBDE and PCB congeners to interfere with TH function.…”
Section: Discussionmentioning
confidence: 99%
“…Only one recently published study from Sweden with relatively large sample size (n = 60, 2 yr −18 yr) showed significantly higher BDE-99, -153, and -183 levels in cats with thyroid disorders after adjusting for cat's age. 36 In the present study, we sampled 22 older cats with age ≥10 yr during 2012−2013 (referred to as the second time period) to compare their PBDE levels to those we reported in our earlier study (sampled in 2008−2010 and referred to as the first time period). 10 We also compared PBDE as well as PCB and OCP levels based on their thyroid status (HT vs non-HT) to better understand the possible links between serum contaminant levels and cat HT.…”
Section: ■ Introductionmentioning
confidence: 94%